Facile Synthesis of Eco‐Friendly Silver@Graphene Oxide Nanocomposite for Optical Sensing. Issue 5 (1st February 2023) - Dat, Nguyen Minh; Cong, Che Quang; Hai, Nguyen Duy; Huong, Le Minh; Nam, Nguyen Thanh Hoai; Tinh, Dang Quoc; Tai, Le Tan; An, Hoang; Duy, Mai Quoc; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this study, silver nanoparticles‐doped graphene oxide (AgNPs@GO) nanocomposite was green synthesized using the extract of Curcuma longa as an effective reducing and stabilizing agent.. Characterization of AgNPs and AgNPs@GO were thoroughly examined via several analysis methods. Thereby, the results show the successful formation as well as the uniform distribution of spherical nano‐sized silver fragments on the GO surface with an average size of 21.14 ± ${± }$ 3.21 nm. The materials were then tested regarding their optical sensing for H2 O2 and Hg 2+ . In specific, AgNPs@GO indicated a great colorimetric detection towards H2 O2 and Hg 2+ with a remarkably low detection limit at 0.48 and 0.158 μM, respectively. Conclusively, AgNPs@GO nanocomposite poses a high potential in application sectors of the colorimetric sensor. Abstract : Silver@Graphene Oxide nanocomposite was successfully fabricated using the abundant and eco‐friendly source of Curcuma longa . The resulting material possesses an even distribution of silver nanoparticles with a great colorimetric performance towards H2 O2 and Hg 2+